Perubahan sosial-ekonomi masyarakat pasca pengembangan destinasi wisata Ayu Rezeki Park Probolinggo - Nourma Ulva Kumala Devi; Supriyanto Supriyanto; Rr. Setyani Hidayati; Vadhea Nuraliza; Kristiyono Kristiyono; Moch.Saifur Rizal; Uswatul Hasanah; Alisyia Putri Melani; MH Rizqi Ramadhani (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
The development of the Ayu Rezeki Park Tourism Destination brought a breath of fresh air to the people's economy in Kerpangan Village, Probolinggo Regency because the true economic vibrancy of the people began to grow and experience changes after the presence of this tour. The village has attractive natural resources and potential for development. In addition, it is also supported by the social and cultural life of the local community which is very harmonious while maintaining noble values and local wisdom. The development of Ayu Rezeki Park tourism certainly has a positive impact and is able to improve the economic welfare of the community. This study aims to analyze the socio-economic changes in the people of Kerpangan Village both from the aspect of employment, community participation in tourism development, to aspects of increasing the community's economic welfare. The method used in this research is qualitative method. Data collection techniques used are interviews, observation and documentation. Data analysis techniques use a case study approach. The results of this study indicate that the developed Ayu Rezeki Park tourism has a significant positive impact on socio-economic changes in the community. Especially from opening job opportunities not only from the agricultural sector but now increasing in the tourism sector, an increase in the number of tourist visitors is able to open business opportunities for MSMEs, & the participation of local communities in supporting the optimization of tourism in order to create more empowered rural communities.